Porcine endometrial heat shock proteins are differentially influenced by pregnancy status, heat stress, and altrenogest supplementation during the peri-implantation period. (1st July 2022) - Adur, Malavika K; Seibert, Jacob T; Romoser, Matthew R; Bidne, Katie L; Baumgard, Lance H; Keating, Aileen F; Ross, Jason W
Abstract: Heat stress (HS ) deleteriously affects multiple components of porcine reproduction and is causal to seasonal infertility. Environment-induced hyperthermia causes a HS response (HSR ) typically characterized by increased abundance of intracellular heat shock proteins (HSP ). Gilts exposed to HS during the peri-implantation period have compromised embryo survival, however if (or how) HS disrupts the porcine endometrium is not understood. Study objectives were to evaluate the endometrial HSP abundance in response to HS during this period and assess the effect of oral progestin (altrenogest; ALT ) supplementation. Postpubertal gilts ( n = 42) were artificially inseminated during behavioral estrus ( n = 28) or were kept cyclic ( n = 14), and randomly assigned to thermal neutral (TN ; 21 ± 1 °C) or diurnal HS (35 ± 1 °C for 12 h/31.6 ± 1 °C for 12 h) conditions from day 3 to 12 postestrus (dpe ). Seven of the inseminated gilts from each thermal treatment group received ALT (15 mg/d) during this period. Using quantitative PCR, transcript abundance of HSP family A (Hsp70) member 1A ( HSPA1A, P = 0.001) and member 6 ( HSPA6, P < 0.001), and HSP family B (small) member 8 ( HSB8, P = 0.001) were increased while HSP family D (Hsp60) member 1 ( HSPD1, P = 0.01) was decreased in the endometrium of pregnant gilts compared to the cyclic gilts. Protein abundance of HSPA1A decreased ( P = 0.03) in pregnant gilt endometrium due to HS, while HSP family B (small) member 1 (HSPB1) increased ( P = 0.01) due to HS. Oral ALT supplementation during HS reduced the transcript abundance of HSP90α family class B member 1 ( HSP90AB1, P = 0.04); but HS increased HSP90AB1 ( P = 0.001), HSPA1 A ( P = 0.02), and HSPA6 ( P = 0.04) transcript abundance irrespective of ALT. ALT supplementation decreased HSP90α family class A member 1 (HSP90AA1, P = 0.001) protein abundance, irrespective of thermal environment, whereas ALT only decreased HSPA6 ( P = 0.02) protein abundance in TN gilts. These results indicate a notable shift of HSP in the porcine endometrium during the peri-implantation period in response to pregnancy status and heat stress. Lay Summary: Heat stress (HS ) deleteriously affects multiple components of porcine reproduction and causes seasonal infertility. Environment-induced hyperthermia causes a HS response (HSR ) typically characterized by increased abundance of intracellular heat shock proteins (HSP ). Gilts exposed to HS during the peri-implantation period have compromised embryo survival, however if (or how) HS disrupts the porcine endometrium is not understood. Study objectives were to evaluate the endometrial HSP abundance in response to HS during this period and assess the effect of oral progestin (altrenogest; ALT ) supplementation. We evaluated the abundance of HSP90, HSP70, HSP60 and HSPB in the porcine endometrium during the peri-implantation period. We demonstrate how a physiological event such as pregnancy and an environmental stressor such as HS, individually and in combination, alter the endometrial abundance of these HSP. Moreover, supplementation of pregnant gilts subjected to HS with ALT also altered the abundance of these HSP in the porcine endometrium. Abstract : Heat stress (HS) causes economic losses to the swine industry by compromising reproduction during summer months. This research study reports the changes observed in porcine endometrial heat shock protein (HSP) milieu during the peri-implantation period in response to pregnancy status and in conditions of HS.